Method and Algorithm for Determining the Hydrodynamic Pressure of Water on the Pressure Face of the Dam Under Seismic Impact - Misliddinovich, Qodirov Fazliddin; Munirovna, Abdullayeva Surayyo; Anatolyevna, Borisova Elena; Yuryevna, Amurova Natalya (European Journal of Life Safety and Stability (2660-9630), 2022)
Ensuring the strength, reliability and efficiency of hydraulic structures requires comprehensive consideration of the static and dynamic loads acting on the structure in a single statement. When calculating the seismic effects of structures such as ground dams that perceive water pressure, in addition to seismic inertial forces, it is necessary to take into account the hydrostatic and hydrodynamic pressure of water on the pressure face, as well as the pore pressure in the body of the dam as a multiphase medium. Currently, consideration of seismic water pressure is mandatory when designing hydraulic structures, because our republic is located in a seismically active area. The purpose of this article is to describe a methodology for taking into account the hydrodynamic pressure of a liquid during seismic impacts on a dam without fastening plates, taking into account the interaction of the liquid and the skeleton of the soil.